Persistent effects of acute trauma on Pavlovian-to-instrumental transfer - Derman, Rifka C.; Lattal, K. Matthew (Frontiers in Behavioral Neuroscience, 2022)
In humans, an acutely traumatic experience can lead to post-traumatic stress disorder (PTSD), which is often characterized by changes in anxiety and motivation months after trauma. There are few demonstrations of the persistent motivational effects of an acute stressor in rodent approaches to PTSD. In two experiments, we evaluated the persistent effects of a battery of footshocks in one context on appetitive Pavlovian conditioning, instrumental learning, and Pavlovian-to-instrumental transfer (PIT) in a different context. In Experiment 1, a battery of footshocks before appetitive training caused deficits in single-outcome PIT (SO-PIT) in male Long Evans rats. The same battery of footshocks after appetitive training, but before testing had little effect on single-outcome PIT overall, but there were some deficits in within-stimulus expression of SO-PIT. In Experiment 2, the battery of footshocks had no effect on sensory-specific PIT in male or female rats, but two sex differences emerged: males showed more generalized fear from the aversive to the appetitive context compared to females, and females showed less evidence for sensory-specific PIT compared to males. Males showed robust sensory-specific PIT, with clear extinction and spontaneous recovery of the sensory-specific PIT effect across test sessions. These findings show that (a) an acute trauma can have persistent effects on general motivational processes and (b) in sensory-specific PIT, females may show transfer through generalized motivational processes, whereas males may rely on specific features of the cues and outcomes to augment instrumental responding selectively. We discuss implications for current approaches to stress and motivation in preclinical approaches to PTSD.